2004
DOI: 10.14356/kona.2004014
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-fed Aerosol Reactors for One-step Synthesis of Nano-structured Particles

Abstract: Aerosol technology is the key process for large-scale production of nano-structured materials such as carbon black, titania and silica. The understanding of gas-phase synthesis was transferred successfully from classic vapor-fed f lames to liquid-fed aerosol reactors, enabling now also the one-step production of demanding and highly functional products. Such aerosol-derived nano-structured metal oxides, mixed metal oxides, and metals on metal oxides find application in the fields of catalysis, sensors, fillers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 95 publications
0
64
0
3
Order By: Relevance
“…Purwanto et al (2011) and Trommer and Bergmann (2015). The several alternative reaction schemes and particle formation mechanisms occurring in the FSP reactor when fabricating, e.g., metal oxide powder, has been discussed on a general level by Mädler (2004).…”
Section: Methods Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Purwanto et al (2011) and Trommer and Bergmann (2015). The several alternative reaction schemes and particle formation mechanisms occurring in the FSP reactor when fabricating, e.g., metal oxide powder, has been discussed on a general level by Mädler (2004).…”
Section: Methods Descriptionmentioning
confidence: 99%
“…Especially flame methods are considered to be optimal for up-scaling (Kammler et al, 2001a;Stark and Pratsinis, 2002;Mueller et al, 2003). Thorough reviews on the flame spray pyrolysis (FSP) techniques for producing nanopowder have been made previously (Pratsinis, 1998;Mädler, 2004;Teoh et al, 2010). The FSP method generates well-defined nanoparticulate material which can be collected as a powder from the exhaust aerosol of the flame (Stepuk et al, 2013;Park and Park, 2015) or sprayed on a surface (Mishra et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2 Spray pyrolysis is a versatile processing technique for preparation of dense and porous single and multi-layered films, ceramic coatings and powders of various materials and morphologies. 61 Classification of different spray processes could be made based on the type of energy source for the precursor reaction such as spray pyrolysis in a tubular reactor (SP), vapor flame reactor (VFSP), the emulsion combustion method (ECM) and flame spray pyrolysis (FSP) 62 or the method of atomizing the precursor, namely air pressurized, electrostatic and ultrasonic spray pyrolysis 63 . In the case that the energy source for precursor reaction is an external energy supply and not from the spray itself, (as in SP and VFSP), method is less sensitive to the choice of precursors and solvent.…”
Section: Thin Film Deposition Techniquesmentioning
confidence: 99%
“…In the case that the energy source for precursor reaction is an external energy supply and not from the spray itself, (as in SP and VFSP), method is less sensitive to the choice of precursors and solvent. 62 .…”
Section: Thin Film Deposition Techniquesmentioning
confidence: 99%
“…FSP is usually applied for the preparation of metal and metal-oxide nanoparticles [37,38]. Recently it has been shown that also nanosized salts such as carbonates, phosphates and halogenides can readily be made by flame synthesis [39][40][41].…”
mentioning
confidence: 99%